Analysis and Improvement of Key Distribution Scheme for Secure Group Communication - Jia Ning Luo; Ming Hour Yang (Journal of Electrical and Computer Engineering)
In a secure group communication, messages between a group coordinator and members are protected by session keys. If a group’s membership changes, the session keys should be updated to insure forward secrecy and backward secrecy. Zhou and Huang proposed a key-updated scheme based on ciphertext-policy attribute encryption algorithm to improve the security of key-update mechanism, but their scheme is vulnerable: a malicious group member may send forged key-update messages to control the group. In this paper, we analyze the vulnerability in Zhou and Huang’s scheme and propose an enhanced scheme. In our scheme, only the group initiator can update group keys and the verification of key-update mechanism is improved to prevent malicious insiders from controlling the group. We also give a security and performance analysis of our scheme.